Hobby and part‐time farmers in a multifunctional landscape: Environmentalism, lifestyles, and amenity. (3rd May 2022) - Song, Bingjie; Robinson, Guy M; Bardsley, Douglas K
Abstract: Hobby and part‐time farming have become important elements of agricultural development in peri‐urban areas of developed countries. Although there has been renewed interest recently in examining the characteristics of this farming, studies have rarely attempted to consider its role in transitional multifunctional landscapes. This article reports on research in the Adelaide Hills, South Australia, using surveys and semi‐structured interviews to examine contributions of hobby and part‐time farmers to an evolving multifunctionality. Hobby farmers are often recent, well‐educated migrants transferring capital from urban areas to the peri‐urban fringe. They engage in various on‐farm and off‐farm activities, with an emphasis on pro‐environmental actions and/or keeping horses. In contrast, part‐time farmers commonly have a farming background and are often transitioning out of farming while retaining farm‐based enterprises representing up to half their household income. While hobby farmers are seeking amenity value from the fringe, part‐time farmers are a more integral component of the conventional rural economy. A re‐evaluation of the importance of the growing numbers of hobby and part‐time farmers is vital as urbanisation pressures increase in peri‐urban fringes of major Australian cities. These farmers represent an important bulwark against urban sprawl, helping to retain agricultural and environmental land uses on the fringe. Abstract : Hobby and part‐time farmers are making distinctive contributions to the evolving multifunctional landscape of the Adelaide Hills, South Australia. The importance of these farmers needs re‐evaluating as they may represent an important bulwark against urban sprawl, helping to retain agricultural land use on the peri‐urban fringe.